Introduction: Moving Forward Post-Hurricane Dorian: The Necessity for Public, Private, and Individual Collaboration in the Face of Climate Change - Bethell-Bennett, Ian A.; Fürst, Saskia M. (International Journal of Bahamian Studies, 2021)
As the articles in this special section of the International Journal of Bahamian Studies focusing on the impacts of Hurricane Dorian note, The Government of The Bahamas can no longer be so lax in its preparation strategies for managing natural disasters, and private companies, non-governmental organizations, and individuals must be included in both the preparation and recovery from such disasters, at national and international levels. Furthermore, support structures should be in place for those very volunteers and individuals who are directly and indirectly affected to alleviate the emotional and psychological trauma surviving and supporting survivors of such events can cause. The Bahamas, like other Small Island Developing States (SIDS), is especially vulnerable to the effects of climate change; therefore, understanding and learning from the lack of preparedness and the ongoing responses to the impacts of Hurricane Dorian will prove crucial for better preparation for future disasters due to global warming.